Emerging technologies to control Brettanomyces spp. in wine: Recent advances and future trends. (May 2020) - Pinto, L.; Baruzzi, F.; Cocolin, L.; Malfeito-Ferreira, M.
Abstract: Background: The application of emerging technologies for the food preservation is a relevant topic for the industry; these technologies are highly efficient to reduce the growth of spoilage microorganisms as well as the production of undesirable microbial metabolites in foods and the processing environment. Spoilage caused by the yeast metabolic activity affects the wine marketability. These novel technologies can be easily implemented during dynamic and customized winemaking processes, in order to control the microbial contaminations and to preserve the wine quality. Scope and approach: During the last two decades, the Brettanomyces spp. contamination in the bottled wines and the winery environment has attracted interest due to production of the volatile phenol compounds, the high stress resistance and the peculiar metabolic features. The use of the emerging technologies, such as high hydrostatic pressure, ultrasounds, pulsed electric fields, UV irradiation, microwaves, ozone and electrolyzed water, novel finishing agents, and biotechnological approaches resulted useful to reduce the contamination levels and the production of off-flavours. In addition, the application of the emerging technologies allowed the reduction of sulphur dioxide, considering its allergenic properties and the raise of Brettanomyces spp. resistance to this compound. The effect of these technologies on nutritional and sensory properties of wines is also discussed. Key findings and conclusions: This review highlights some useful novel approaches to control Brettanomyces spp. during winemaking, allowing the producers to follow the "hurdle concept" and to minimize wine sensory changes. Graphical abstract: Image 1 Highlights: Evaluation of the antimicrobial effect of emerging technologies on Brettanomyces spp. Control of volatile phenols production through the emerging technologies application. Description of the biotechnologies approaches to control Brettanomyces spp. Application of these emerging technologies for the barrel sanitation. Brettanomyces spp. risk assessment based on novel analytical tools.